Pengimplementasian Kebijakan Desentralisasi Dan Otonomi Daerah Terhadap Hubungan Keuangan Daerah Pusat dan Daerah - Kartika, Anggi Aulia; Sitorus, Annisa Mardiah; Siagian, Putry Adelina; Panjaitan, Rohana; Lubis, Putri Kemala Dewi (Universitas Pahlawan Tuanku Tambusai, 2023)
The effects of decentralization and regional autonomy on Indonesia's federal-regional financial ties are the subject of this brief study. Patterns of financial interactions in the implementation of regional autonomy, changes to statutory rules, and the history of central and regional financial legislation are all part of the issue. The development of efficient financial systems requires substantial work, but regional autonomy also affords regions the chance to boost their own financial performance. The structure of central-regional financial connections may be affected by decentralization and regional autonomy policies; how prepared institutions are, available human resources, financial management systems, and budget submission procedures are all crucial factors to consider. Implementing decentralization and regional autonomy policies in Indonesia is expected to have a good influence on financial ties between the center and regions if these aspects are carefully considered.